Vaccine hesitancy in Western and Eastern Europe: The significance of contextual influences - Trifunović Vesna (Glasnik Etnografskog Instituta SANU, 2022)
Using the example of Eastern and Western Europe, the paper points out the importance of contextual influences on decisions and behaviour regarding vaccines and vaccination. Contextual determinants have been identified as important in theorizing the concept of vaccine hesitancy that allows for a comprehensive understanding of the reasons why the public questions vaccines. Therefore, the paper first presents the theoretical elaboration of the aforementioned concept, and then discusses the contextual influences on vaccine hesitancy within the European region in order to showcase the differences that exist in this respect between Western and Eastern Europe, as well as between certain minority communities and the majority population in some Western European countries. In all cases, vaccine hesitancy appears to be a matter of trust which has been further eroded by social, political and economic experiences characteristic for the post-socialist context in Eastern Europe and the conditions in which some minority communities live in Western Europe. The theoretical framework of the concept of vaccine hesitancy is presented according to the report of the SAGE Working Group on Vaccine Hesitancy, while the presentation of contextual determinants is based on the results of quantitative and qualitative research in different European countries and reviews of studies that focus on these influences.